Keenan Zeller: capstone - Zeller, Keenan, artist (Colorado State University. Libraries, 2016)
The artist's statement: As a small child I was fascinated by nature and made a point to surround myself in its beauty. I had a very strange childhood. I was often getting into trouble and acting out in unique ways, which made my parents worry. On road trips I made my mother pull over when we passed a cemetery. I would lose myself wandering around the grassy fields with cement tombstones and flowers, both dead and alive. I was interested in the dead as much as I was with the living. I was the perfect blond hair blue eyed child with an unusual interest in death. This led me to have an appreciation for life and the fragility of living things. My work is made from a durable material that is easily manipulated. It can become a fragile, delicate object such as a rose petal, or can be a strong sturdy object. There are endless possibilities with clay. I have the ability to make something feel alive. Being present with the clay and pushing myself to see how far I can't make it is not only thrilling but gives me a sense of power in the studio, a sacred space. Feeling and manipulating the material to surrender to my touch and pressure allows me to provoke different ideas. There is a sense of being present, and there can be times of absence. Each stroke or touch, intentional or not is embedded in the material and remains once fired. The mark of the hand or tool dictates even more pattern and detail I aim to show in my work. This gives my work the ability to feel alive or dead, stagnant or dynamic. This gives the voids in my work a purpose, they become mysterious, eerie, and one may get lost.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery